Morfologi Bahasa Indonesia - Putref Murefit Budiman (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This research examines the morphological aspects of Indonesian with a focus on the process of word formation and changes in morphological structure in contemporary Indonesian language use. The aim of this research is to identify and analyze various morphological processes that occur in Indonesian word formation, as well as to reveal productive patterns of word formation in the development of modern Indonesian. This research uses a qualitative descriptive method with a morphological approach. Data was collected using skill-free listening (SBLC), note-taking techniques and documentation techniques from various written sources. Data analysis was carried out using the agih method using the technique for direct elements (BUL), loss technique, replace technique, and expand technique. The results of the research show that: (1) the affixation process is the most productive morphological process in Indonesian word formation, (2) new patterns were found in the reduplication process which reflect the dynamics of language development, (3) the composition process shows a tendency to form compound words which increasingly complex along with modern communication needs. This research provides theoretical contributions in the development of Indonesian language morphology studies and practical implications for Indonesian language learning.